2013
DOI: 10.3851/imp2760
|View full text |Cite
|
Sign up to set email alerts
|

HCV RNA Quantification with Different Assays: Implications for Protease-Inhibitor-Based Response-Guided Therapy

Abstract: Lower rates of undetectable HCV RNA with ART at week 4 suggest that if RGT criteria are determined with ART, the proportion of patients qualifying for shorter treatment duration may be significantly lower (26%). Therefore, different RGT criteria may be necessary for ART to maximize numbers benefiting from shortened treatment. Further testing and validation are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 19 publications
6
18
0
Order By: Relevance
“…Although our study did not include repeated measurements of samples to address assay variability and the treatment duration decision was predefined based on the HPS assay used in the OPTIMIZE study, the data presented here are in line with the results of the comparison of the HPS and ART assays on samples from patients treated with other DAAs combined with Peg-IFN/ RBV therapy (16,17). These studies also suggested that 12 IU/ml is a more appropriate cutoff for response-guided treatment for a DAA-based triple therapy when the ART assay is used for HCV RNA quantification.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Although our study did not include repeated measurements of samples to address assay variability and the treatment duration decision was predefined based on the HPS assay used in the OPTIMIZE study, the data presented here are in line with the results of the comparison of the HPS and ART assays on samples from patients treated with other DAAs combined with Peg-IFN/ RBV therapy (16,17). These studies also suggested that 12 IU/ml is a more appropriate cutoff for response-guided treatment for a DAA-based triple therapy when the ART assay is used for HCV RNA quantification.…”
Section: Discussionsupporting
confidence: 66%
“…Discordant results between the assays were mostly observed in samples with values bordering the LOQ and LOD. As previously reported, the ART assay demonstrated higher sensitivity for detection of the HCV load in the low range than the HPS assay (16,17,23). Overall, for 15% of patients who had no viral RNA detected by HPS, RNA was still detectable by ART.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Interestingly, the assay is more sensitive around the lower limit of quantification (LLOQ) when compared to the CAP/CTM and HPS/CTM assays. This has led to the observation that many on-treatment or even post-treatment specimens that had results reported as ''target not detected" by HPS/CTM or CAP/CTM showed detectable/not quantifiable or even quantifiable results by the ART assay [22,[39][40][41][42].…”
Section: Real-time Pcr Technologymentioning
confidence: 96%
“…Thus, eligibility for shortened therapy should be based on attainment of undetectable HCV RNA at week 4 only, whereas patients with detectable/not quantifiable (<25 IU/ml) HCV RNA should receive a full course of therapy [43]. However, the HPS/CTM assay that was used in these trials has been shown to be less sensitive compared to CAP/CTM and ART, which are mostly used in clinical routine [39,44,57]. Indeed, some data suggest that assay-specific RGT criteria may be required given the significant performance differences among HCV RNA assays.…”
Section: The Role Of Hcv Rna Quantification During Protease Inhibitormentioning
confidence: 98%